Flow training program: mindfulness, decision making, and mental well-being of young and adult elite handball athletes - Martiny, L.; Dias, G.; Ferreira, J. P.; Mendes, R.; Mendes, R. (Sports, 2024)
This study aimed to analyze the effect of a flow training program based on mindfulness applied to young and adult elite handball athletes. A quantitative, quasi-experimental, descriptive data analysis approach was carried out. The sample included 105 athletes (51 female and 54 male). The athletes were divided into two groups: (i) experimental (n = 53) and (ii) control (n = 52). The results of the repeated ANOVA indicated that the experimental group achieved significant improvements compared to the control group in decision making (n2p = 0.086), mental well-being (n2p = 0.045), dispositional flow state (n2p = 0.103), non-judgment (n2p = 0.040), refocusing (n2p = 0.052), and mindful traits in daily life (n2p = 0.058). A Pearson analysis demonstrated a positive correlation between dispositional flow state and mindfulness in sport and mental well-being. The correlation analysis also showed an inverse correlation between decision making and sense of control and mindful traits in daily life. The findings revealed that the program can be effective in decision making, mental well-being, dispositional flow state, mindfulness in sport, and mindful traits in daily lives of athletes